RANCANG BANGUN KOMPOSTER AEROB DAN ANAEROB UNTUK MENGURANGI SAMPAH ORGANIK RUMAH TANGGA - Robert Sinaga; Julieta Christy; Ruth Dameria Haloho (Universitas Quality, 2021)
This objective of this study was design and manufacture a simple drum compost reactor (composter) to be able to process organic waste into compost so as to reduce the problem of organic waste towards generation-z let’s go organic in the orphanage sinar indah cahaya bersama. The method used was engineering or modification, design research activities that are not routine so that contributions are generated in the form of processes and products. The result of the composter was vertical type aerobic composter drum without mixing system with parts up cover, composting room, filter, filter support posts, leachate chamber (liquid organic fertilizer), pipes and air vents covered with gauze, solid compost discharge holes and faucet dispensing liquid organic fertilizer.